2016
DOI: 10.1175/jhm-d-15-0089.1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Runoff–Infiltration Partitioning and Resolved Overland Flow on Land–Atmosphere Feedbacks: A Case Study with the WRF-Hydro Coupled Modeling System for West Africa

Abstract: The analysis of land–atmosphere feedbacks requires detailed representation of land processes in atmospheric models. The focus here is on runoff–infiltration partitioning and resolved overland flow. In the standard version of WRF, runoff–infiltration partitioning is described as a purely vertical process. In WRF-Hydro, runoff is enhanced with lateral water flows. The study region is the Sissili catchment (12 800 km2) in West Africa, and the study period is from March 2003 to February 2004. The WRF setup here in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
122
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 100 publications
(132 citation statements)
references
References 99 publications
8
122
2
Order By: Relevance
“…Also, to improve the representation of the diurnal cycle of precipitation and of extreme precipitation events in the models, convectionpermitting and coupled atmospheric-hydrological modelling experiments are pursued (Arnault et al, 2016;Klein et al, 2017;Naabil et al, 2017). The climate modelling efforts presented here are undertaken in parallel to the setup of a dense network of automatic weather stations in the region with the goal of assessing and reducing model uncertainties and biases.…”
Section: Discussionmentioning
confidence: 99%
“…Also, to improve the representation of the diurnal cycle of precipitation and of extreme precipitation events in the models, convectionpermitting and coupled atmospheric-hydrological modelling experiments are pursued (Arnault et al, 2016;Klein et al, 2017;Naabil et al, 2017). The climate modelling efforts presented here are undertaken in parallel to the setup of a dense network of automatic weather stations in the region with the goal of assessing and reducing model uncertainties and biases.…”
Section: Discussionmentioning
confidence: 99%
“…These previous studies suggest that coupled atmospherichydrological modeling significantly affects the simulated atmospheric-terrestrial water balance (Maxwell et al 2011;Senatore et al 2015;Arnault et al 2016;Wagner et al 2016), especially in arid and semi-arid regions where soil moisture-precipitation interactions are largest (e.g., Findell and Eltahir 2003;Koster et al 2004;Anyah et al 2008). It is against this background that this study applies the coupled WRF-Hydro modeling system for the Mathioya-Sagana subcatchment (MSS) in the upper TRB, Kenya.…”
Section: Introductionmentioning
confidence: 98%
“…In a two-way coupling, the feedback is allowed, which leads to production of subgrid scale land surface fluxes and generally an improvement of model simulations (Zabel and Mauser 2013). It is argued that the coupled modeling approach has the advantage of including the soil moisture redistribution feedback in the lower boundary conditions of atmospheric models, which may lead to an improved representation of water and energy fluxes between land and atmosphere (Maxwell et al 2011;Shrestha et al 2014;Senatore et al 2015;Arnault et al 2016;Wagner et al 2016). Maxwell et al (2007) showed that the fully coupled modeling system yields a topographically driven soil moisture distribution and depicts a spatial and temporal correlations between surface and lower atmospheric variables and water depth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations